On the Question of the State of Knowledge of Foreign Language Training in the Higher Education System in Ukraine - Nitenko, Olha (Pedagogical Discourse, 2015)
The article presents a brief review of scientific works of Ukrainian scientists, which are dedicated to the state of study of the foreign language training of specialists in various fields in higher education system of Ukraine in the period from 2005 to 2015 year. In particular, this is the development of scientific and methodological foundations of the system of professional Business English training of civil servants; the definition of pedagogical conditions of teaching foreign languages for future software engineers through multimedia programs; the representation of an integrated scheme of the classification of models of distance learning, with using its components the institution can create your own model regardless of its needs and opportunities; the implementation of scientific and pedagogical analysis of the problem of the use of foreign language mass media sources in the theory and practice of future journalists training; the presentation of the theory and technology of formation of professional foreign language competence of future Natural Sciences specialists; the coverage of theoretical and methodological problems of formation of professional foreign language competence of students in higher technical educational institutions in distance education; the exercise of professional foreign language training description of future specialists in information and communication technologies in technical universities; as well as the implementation of a comprehensive analysis of foreign language training of economics students in the context of globalization. The article justified the necessity of studying and modernization of the foreign language training of the Ukrainian experts in law taking into account the European experience.